PERKEMBANGAN EMBRIO DAN PERFORMA AWAL LARVA IKAN TENGADAK (Barbonymus schwanennfeldii) - Fitra Yani; Cahyanti W (Universitas Djuanda, 2021)
This experiment was conducted from May 2021 – September 2021 at the Freshwater Fishery Germplasm Research Installation in Cijeruk, Bogor, West Java. This study aimed to determine the stages of embryonic development and early larval performance that occurred in Tengadak fish (Barbonymus schwanenfeldii). This experimental study used two female fish, two male fish, and anaesthetic drugs. Parameters observed included observation of embryos and early performance of squirrelfish larvae. The embryo data were analyzed in a qualitative descriptive manner with pictures of each egg development phase and then data on egg hatching time. The results showed that the early development of the embryo in trout generally includes cleavage stages, morula, blastula (blastoderm formation), gastrula (closure of the yolk sac), segmentation and hatching. The initial performance of the scorpion fish larvae reared at a temperature of 28oC showed an abnormality value of 5.7±2.5%. The average diameter of the egg yolks of the tee-fish was 39.42±4.41 µm, and the average initial length of the trout larvae was 18.46±1.32 µm.